Full house : an invitation to fractions - Dodds, Dayle Ann.; Carter, Abby (Somerville, Mass. : Candlewick Press, 2009)
A rhyming introduction to fractions in which Miss Bloom, proprietor of the Strawberry Inn, discovers five guests eating her cake in the middle of the night.
Booklist
School Library Journal
Wilson's Children
2.3
K-3
K-3
Keywords: Fractions -- Juvenile literature; Fractions; Fractions